Literacy and instrumental activities of daily living: an evident relationship (Revista Educação, Artes e Inclusão, 2022)
The purpose of this article is to identify the relationship between literacy and Instrumental Activities of Daily Living (IADL). The study was characterized as a bibliographic research, of a conceptual character put in to circulation based on a doctoral research. For this purpose, it was mainly used references from the área of Education and Psychology, which allowed to encourage the discussion about the implications of literacy for the autonomy of the person with cognitive deficit. The results of the study showed that there is na evidente relationship between literacy practices and the performance of instrumental tasks of daily living. The differentiation between IADLs and Activities of Daily Living (ADLs) are some of the highlights of this essay. Like any initiative of a scientific nature, the proposal for this new perspective has a general character, insofar as it constitutes na action of a broad, and at the same time, specific nature, which aims to offer theoretical principles and initial guidelines for the relationship between practices of literacy related to the use of Daily Living Instruments.
Keywords: Literacy; Instrumental Activities of Daily Living; Autonomy